A 2e Parent's Journey: Persistence, Partnership, and the Provision of Unconditional Love. (October 2015) - Brownstein, Michelle
I have four children, three of whom are twice exceptional in the context of the new Community of Practice (2e CoP) definition highlighted in this issue. I share a personal story of a parent's journey in persistence, partnerships, and the provision of unconditional love.